Self‐Limiting Assembly of Au Nanoparticles Induced by Localized Dynamic Metal‐Phenolic Interactions. Issue 47 (17th November 2020) - Su, Jiaojiao; Huang, Xin; Yang, Ming
Abstract : Dynamic nanoparticle assembly represents an important platform for the creation of functional materials with stimuli‐responsive properties. In this work, we show that small Au nanoparticles (ca. 5 nm) with mixed surface ligands (citrates and tannic acid) may be assembled into quasi‐sphere‐like superstructures (ca. 50 nm) induced by the presence of ferric ions. The spontaneous self‐limiting assembly is enabled by the localized metal‐phenolic interactions as a result of the possible phase separation of citrates and tannic acid on the surface of Au nanoparticles, restricting the growth of ionic cross‐linking network. The disassembly may be further achieved by adding ethylenediaminetetraacetic acid as a stronger chelation ligand for ferric ions, allowing the reversible assembly and disassembly of Au nanoparticles. Our results provide new insights into the design of dynamic plasmonic assemblies by manipulating the nature of surface ligands. Abstract : Au nanoparticles with segregated surface ligands can self‐assemble into quasi‐sphere‐like superstructures. Such self‐limiting assembly is induced by the localized metal‐phenolic interactions, which also allow the reversible assembly and disassembly of Au nanoparticles by introducing competing ligands.